Os labirintos da cidade: Marcial em Roma - Torrão, João Manuel Nunes (2008)
Martial had unparalleled knowledge of the city of Rome and he provides guidance to todays’s readers in the street maze of the city. That city had specific feaures which made the circulation of people and vehicles difficult, in spite of the efforts made by some politicians to improve the urban network.